ANALISIS KALIMAT TANYA DALAM BAHASA NIAS SELATAN DIALEK TELUK DALAM DESA HILIGANÖWÖ - Agnes Ewin Gaurifa (Universitas Nias Raya, 2024)
Based on the background of the problem, this researchs is unique in that partial interrogative sentences begin with the letter H and total interrogative sentences begin with the letters M, H, G, and S. the aim of this researchs is to describe the form of partial interrogative sentences in the South Nias language, Teluk Dalam dialect. Hiliganöwö village and total interrogative sentences in South Nias language, Teluk Dalam dialect, Hiliganöwö village. This type of researchs is qualitative researchs with descriptive methods. The objects of this researchs are traditional leaders and several Hiliganöwö Village communities with the number of informants being four (4) people with an age range of 40-60 years. The data colletion technique is a semi- structured interview technique. The data analysis technique in this researchs are data reduction, data display, and verification. The results of this research show that in Hiliganöwö village there are partial question sentences forms that begin with letter H, namely Hadia, Haega, Hamega, Hanata, Hana, and Haegaiwaisa. And the total interrogative sentence form begins with the letters M, H, G, and S, namely moguna khou embe anda wa?, Hadia mamoi ndraugö mowoli barabara ba fasa wa?, gömöi ba fasa mahemolu wa?, so khömi mböra wa?. The suggestions put forward by the researchers are for teachers, this research is used as a comparision material with Indonesian question sentences, and of course it can help students learn the Nias language better.